The - Tudor, Ioana (Oxford University Press, 2008)
The treatment of foreign investors and of their investments on the territory of a host State is often subject to a bilateral investment treaty (BIT) signed by the national State of the investors and the host State. These BITs usually contain a clause in which the two States offer fair and equitable treatment (FET) to the foreign investors on their territory. Moreover, this clause has become a norm of customary law, implying that investors may rely on it even outside the context of the BIT. Foreign investors whose rights under this clause have not been respected may bring the State in front of an international tribunal. This book analyses not only the conventional and customary framework of the FET clause but also its scope and all its applications in the existing case law. It tackles the standard of fair and equitable treatment by applying four conceptual frames: the legal basis of FET, its nature as a standard, its content and finally the implications of its breach